Impact of Alcohol on Bone Health in People Living With HIV: Integrating Clinical Data From Serum Bone Markers With Morphometric Analysis in a Non‐Human Primate Model. (28th November 2022) - Denys, Alexandra; Norman, Allison; Perrien, Daniel S; Suva, Larry J; Simon, Liz; McDaniel, Lee S; Ferguson, Tekeda; Pedersen, Kim; Welsh, David; Molina, Patricia E; Ronis, Martin JJ
ABSTRACT: People living with HIV (PLWH) represent a vulnerable population to adverse musculoskeletal outcomes due to HIV infection, antiretroviral therapy (ART), and at‐risk alcohol use. Developing measures to prevent skeletal degeneration in this group requires a grasp of the relationship between alcohol use and low bone mass in both the PLWH population and its constituents as defined by sex, age, and race. We examined the association of alcohol use with serum biochemical markers of bone health in a diverse cohort of PLWH enrolled in the New Orleans Alcohol Use in HIV (NOAH) study. To explore the effects of alcohol on bone in the context of HIV and ART and the role of estrogen, we conducted a parallel, translational study using simian immunodeficiency virus (SIV) + /ART + female rhesus macaques divided into four groups: vehicle (Veh)/Sham; chronic binge alcohol (CBA)/Sham; Veh/ovariectomy (OVX); and CBA/OVX. Clinical data showed that both osteocalcin (Ocn) and procollagen type I N‐propeptide (PINP) levels were inversely associated with multiple measures of alcohol consumption. Age (>50 years) significantly increased susceptibility to alcohol‐associated suppression of bone formation in both female and male PLWH, with postmenopausal status appearing as an additional risk factor in females. Serum sclerostin (Scl) levels correlated positively with measures of alcohol use and negatively with Ocn. Micro‐CT analysis of the macaque tibias revealed that although both CBA and OVX independently decreased trabecular number and bone mineral density, only OVX decreased trabecular bone volume fraction and impacted cortical geometry. The clinical data implicate circulating Scl in the pathogenesis of alcohol‐induced osteopenia and suggest that bone morphology can be significantly altered in the absence of net change in osteoblast function as measured by serum markers. Inclusion of sophisticated tools to evaluate skeletal strength in clinical populations will be essential to understand the impact of alcohol‐induced changes in bone microarchitecture. © 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.